Why lessons learnt are lost: Understanding the complexity of barriers to Build Back Better in Pakistan. Issue 5 (7th October 2019) - Haris, Muhammad; Cheema, Abdur Rehman; Subasinghe, Chamila
Abstract : Purpose: The purpose of this paper is to reduce the gap in understanding the complexity of barriers, their modifiers and how these barriers and their modifiers result in malpractices and missed good practices in post-earthquake reconstruction contexts. This paper provides insights to the often asked question: why the lessons learnt from one earthquake event are not actually learnt and many of the mistakes around housing reconstruction are repeated? Design/methodology/approach: The paper is based on the review of the literature of the top deadliest earthquakes in the developing countries and the two case studies of the 2005 Kashmir and 2015 earthquake in Pakistan. Findings: Multifarious barriers, their modifiers, malpractices and missed good practices are deeply interwoven, and endemic and include weak financial standing, lack of technical know-how, vulnerable location, social and cultural preference, affordability and availability of materials, over-emphasis on technical restrictions, inefficient policies, lack of clarity in institutional roles, monitoring and training. Research limitations/implications: The study is desk based. Practical implications: A better understanding of barriers can help disaster-related organisations to improve the planning and implementation of post-earthquake housing reconstruction. Social implications: The study contributes to the understanding concerning various social and cultural preferences that negotiate the Build Back Better (BBB) process. Originality/value: The study offers a distinctive perspective synthesising the literature and the two case studies to sharpen the understanding of the complexity of barriers to BBB.